The Top-100 Highly Cited Original Articles on Drug Therapy for Ventilator-Associated Pneumonia - Chao-Yang Wang; Chao-Yang Wang; Chao-Yang Wang; Bing-Hui Li; Bing-Hui Li; Bing-Hui Li; Lin-Lu Ma; Lin-Lu Ma; Ming-Juan Zhao; Ming-Juan Zhao; Ming-Juan Zhao; Tong Deng; et al. (Frontiers Media S.A., 2019)
Background: In recent decades, research on drug therapy for ventilator-associated pneumonia (VAP) remains one of the major hot-spots in the field of critical care medicine, but relevant data are not satisfactory. Our aim was to assess the status and trends of the most cited articles on drug therapy for VAP through bibliometric approaches.Methods: The Institute for Scientific Information (ISI) Web of Science core collection database was searched for the VAP-related articles. The time period for retrieval was from the beginning of the database to September 30, 2018. The top 100 most cited articles were selected to obtain their information on the authors, title, publication, number of citations, author's affiliations, country, etc. These general information and bibliometric data were collected for analysis. VOSviewer software was used to generate a term co-occurrence graph that visualized a reference pattern for different terms in the 100 articles.Results: The number of citations for the 100 selected articles ranged from 142 to 3,218. These articles were published in 31 different journals. The top three journals in terms of the number of our selected articles they published were "Critical Care Medicine" (17 articles), "American Journal of Respiratory and Critical Care Medicine" (11 articles) and "Clinical Infectious Diseases" (10 articles). The most frequently nominated author was Marin H. Kollef from the University of Washington, and of the top 100 articles, 16 listed his name. These top 100 articles were published after the year of 2000. The most common type of article in the top 100 was an original article (53%). The United States and France were the countries that contributed the most articles to the top 100. Gram-negative bacilli, pseudomonas aeruginosa, antibiotics, risk factors and other terms appeared more frequently, suggesting that attentions on this issue currently focused on the rational application and management of antibiotics.Conclusion: This study analyzed the 100 most cited articles on drug-treated VAP, and provided insights into the historical developments and characteristics of the most cited articles in the field of VAP.